2000
DOI: 10.1007/s004670050020
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tolerance of mycophenolate mofetil in renal transplant children

Abstract: Mycophenolate mofetil (MMF) is a prodrug that is hydrolyzed to the active immunosuppressant mycophenolic acid (MPA). The drug is now widely prescribed for adult renal transplant recipients and its use has been extended to pediatric patients, although pharmacological data in this age group are limited. Nine pediatric renal transplant recipients received MMF with corticosteroids and either cyclosporine or tacrolimus a median of 55 months (range 7.5-124 months) months after transplantation. The pharmacokinetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 11 publications
2
42
2
2
Order By: Relevance
“…Although 1A10 deviated significantly from linearity, there is no evidence that MPA exhibited cooperative effects on its activity. Hence, the capacity of MPA to show such an increase by four isozymes no doubt contributes to its high level of glucuronide production in vivo (Ding et al, 1993;Jacqz-Aigrain et al, 2000). Although MPA is highly prescribed because of its highly selective inhibition of IMPDH II and other beneficial effects (Transplantation Study Group, 1996), its extensive metabolism to glucuronides (Ding et al, 1993;Shütz et al, 1999;Jacqz-Aigrain et al, 2000), no doubt, contributes to high glucuronide accumulation in patient blood, which evidently compromises the efficacy of immunosuppression by MPA.…”
Section: Basu Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Although 1A10 deviated significantly from linearity, there is no evidence that MPA exhibited cooperative effects on its activity. Hence, the capacity of MPA to show such an increase by four isozymes no doubt contributes to its high level of glucuronide production in vivo (Ding et al, 1993;Jacqz-Aigrain et al, 2000). Although MPA is highly prescribed because of its highly selective inhibition of IMPDH II and other beneficial effects (Transplantation Study Group, 1996), its extensive metabolism to glucuronides (Ding et al, 1993;Shütz et al, 1999;Jacqz-Aigrain et al, 2000), no doubt, contributes to high glucuronide accumulation in patient blood, which evidently compromises the efficacy of immunosuppression by MPA.…”
Section: Basu Et Almentioning
confidence: 99%
“…Hence, the capacity of MPA to show such an increase by four isozymes no doubt contributes to its high level of glucuronide production in vivo (Ding et al, 1993;Jacqz-Aigrain et al, 2000). Although MPA is highly prescribed because of its highly selective inhibition of IMPDH II and other beneficial effects (Transplantation Study Group, 1996), its extensive metabolism to glucuronides (Ding et al, 1993;Shütz et al, 1999;Jacqz-Aigrain et al, 2000), no doubt, contributes to high glucuronide accumulation in patient blood, which evidently compromises the efficacy of immunosuppression by MPA. Both MPAG and AcMPAG (M2) were observed at high concentrations in the plasma of transplant recipients receiving mycophenolate mofetil Wieland et al, 2000), which indicates that our results are consistent with reports that found AcMPAG in humans.…”
Section: Basu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…19 Jacqz-Aigrain dkk. 2000 melaporkan pada 9 anak berumur (8,2 + 3,5) tahun, 16 Bunchman dkk. 2001 melaporkan pada 100 anak berumur 3 bulan -18 tahun, 21 dan DavidNeto dkk.…”
Section: Pemakaian Mikofenolat Mofetilunclassified
“…Pada 1 pasien terjadi anoreksia berat, penurunan berat badan, diare, dan pada 4 pasien terjadi nyeri abdomen yang mengalami perbaikan setelah dosis dikurangi atau obat dihentikan. 16 Filler dkk. 2003 melaporkan diare pada 1/15.…”
unclassified